'Varietal screening of grasspea (Lathyrus sativus) in presence or absence of Rhizobium inoculation - BHUIYAN, M A; KHANAM, D; KHATUN, M R (The Indian Journal of Agricultural Sciences, 2013)
Grasspea. (Lathyrus sativus L.) varieties '8603', '8604' and 'Jamalpur Local' were inoculated with Rhizobiumstrain RLs 10. Seed inoculation with this bacteria enhance,d nodulation, dry-matter weight and yield of grasspea cultivarsunder field conditions. Results of 3-year observation showed that the advance lines '8603' and '8604' which hadmaximum nodulation did not give a high seed yield and 'Jamalpur Local' recorded maximum seed yield but did notshow high nodulation as in the advance lines '8603' and '8604'. The advance line '8603' produced highest nodulenumber (62.7,52.2 and 39.l/plant), nodule weight (81, 57 and 69 mg/plant) but 'Jamalpur Local' recorded highest seedyield (1.67, 1.48 and 1.73 tonnes/ha) owing to inoculation in 1991-92, 1992-93 and 1993-94 respectively.